Perspectives on student behaviour in schools : exploring theory and developing practice - Wearmouth, Janice (Routledge, 2005)
The authors of this comprehensive text discuss the root causes of disruptive behaviour, tackle assessment issues and develop effective intervention strategies that will be of practical use to teachers and other educators.